2017
DOI: 10.1161/strokeaha.117.017094
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Domain-Specific Health-Related Quality of Life Using Acute Infarct Volume

Abstract: Background and Purpose Limited data exist regarding the relationship between acute infarct volume and health-related quality of life (HRQOL) measures after ischemic stroke. We evaluated whether acute infarct volume predicts domain-specific Neuro-Quality of Life (Neuro-QOL) scores at 3 months after stroke. Methods Between 2012 and 2014, we prospectively enrolled consecutive patients with ischemic stroke and calculated infarct volume. Outcome scores at 3 months included modified Rankin score (mRS) and Neuro-QO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…This observation adds to the notion that reducing the overall stroke burden such as through systemic thrombolysis or mechanical thrombectomy may reduce the risk for poststroke cognitive impairment. 38,39 In addition to infarct volume, location is another important predictor of outcome as suggested by earlier studies. Infarct in cortical location tend to predict poor outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…This observation adds to the notion that reducing the overall stroke burden such as through systemic thrombolysis or mechanical thrombectomy may reduce the risk for poststroke cognitive impairment. 38,39 In addition to infarct volume, location is another important predictor of outcome as suggested by earlier studies. Infarct in cortical location tend to predict poor outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Of note, the size and locations of acute infarct was significantly associated with one or more domains of HRQoL in this study. Consistently, the acute infarcts’ volume was recently found to contribute modestly to the prediction of domains of applied cognition–general concerns of HRQoL, however, this study did not explore the locations of acute infarct (Lin et al, 2017 ). Our study showed that the infratentorial acute infarct could negatively affect several domains of SSQoL, implicating a necessity of incorporation of the locations of infarcts or other brain lesions when investigating their impacts on HRQoL after stroke.…”
Section: Discussionmentioning
confidence: 69%
“…Multivariate linear regression analyses were used to investigate the associations between SVD burden and overall SSQoL and its domains adjusting for age, sex, education, history of stroke, hypertension, diabetes mellitus and hyperlipidemia, scores of NIHSS on admission, BI, HADS-AS, GDS, MMSE, acute infarcts’ volume, acute infarcts’ locations (cortical, subcortical and infratentorial), presence of old infarcts with a forward selection method. Due to the skewness of acute infarcts’ volume, they were categorized into four degrees based on the quartile (Degree 1: = 0 mL; Degree 2: 0.01–0.50 mL; Degree 3: 0.51–1.76 mL; Degree 4: >1.76 mL; Lin et al, 2017 ) and then made them enter all the regression models. The models did not involve any multicollinearity since all predictors showed a variance inflation factor of <10.…”
Section: Methodsmentioning
confidence: 99%
“…18 While prior studies on sex and outcomes after stroke have focused on disability and functional outcomes, our group has not observed differences between men and women in HRQOL after stroke. 3,6 Further work should be done to elucidate why sex impacts on functional outcomes but HRQOL after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that acute infarct volume, a valuable biomarker in predicting disability, was a poor predictor of HRQOL after acute ischemic stroke. 3…”
Section: Introductionmentioning
confidence: 99%